EFFECTS OF HYDROGEN ADDITION INTO INTAKE AIR ON THE HYDROCARBON EMISSION OF GASOLINE ENGINES AT COLD START CONDITION - Hariyanto, Arief; Arismunandar, Wiranto; Engel, Gerard George (Mesin, 2007)
Start process, particularly cold start condition is considered important to be focused in terms of emission reduction due to high unburned hydrocarbon (HC) concentration in the exhaust gas. Several methods have been proposed and implemented for reducing exhaust gas emission during starting condition. In this paper will be discussed the addition of hydrogen into intake air in order to reduce the level of HC emission during cold start condition. Using this method, the combustion process during starting will be improved to produce better combustion. This paper describes an experiment conducted to find the optimal amount of hydrogen added on start process at various coolant temperatures, which is effective to reduce the total HC concentration at each start temperature, respectively. The results show that the HC concentration in the exhaust gas is influenced by the temperature of engine and can be reduced significantly by hydrogen addition into intake air.